Synergistic Effect of Sulfide and Ammonia on Anaerobic Digestion of Chicken Manure - ÇALLI, BARIŞ (SPRINGER, 2019)
The effect of the sulfur load on anaerobic digestion of chicken manure (CM) was investigated in a laboratory scale anaerobic mono-digester at high total ammonia nitrogen (TAN) concentrations. The digester was operated for 268 days by increasing the organic loading rate from 0.5 to 2.5kg-VS/m(3)/day and the total Kjeldahl nitrogen up to 5050mg/l. The CH4 yield of 0.36 +/- 0.02m(3)/kg-VS was achieved at 2.5kg-VS/m(3)/day of loading rate without any inhibition. The results showed that, anaerobic mono-digestion of chicken manure was applicable with the acclimation of microbial consortium to high TAN concentrations. However, when the sulfur content of the CM fed to the digester increased suddenly by coincidence, the CH4 yield decreased about 25% from 0.36 +/- 0.02 to 0.27 +/- 0.03m(3)/kg-VS. As a result, the acetic acid concentration increased from 130 to 1700mg/l showing that the acetate consuming methanogens were detrimentally affected from TAN and total sulfide concentrations above 4000 and 100mg/l, respectively.
Keywords: Ammonia; Anaerobic digestion; Chicken manure; Inhibition; Total sulfide; Sulfur; BIOGAS PRODUCTION; SULFATE REDUCERS; CO-DIGESTION; INHIBITION; METHANOGENS; METHIONINE; FERMENTATION; RECOVERY; KERATIN